Quality Control Analysis at a Screen Printing Workshop Using the FMEA and Fuzzy FMEA Methods at UD. MKKG Gresik - Restu Maulana; Deny Andesta (G-Tech: Jurnal Teknologi Terapan, 2026)
UD. MKKG is a screen printing company facing product defect issues, such as ink not adhering, cracked prints, and imprecise results. This study aims to identify the primary causes of these defects and establish priorities for improving production quality in the screen printing unit. The research method used is the integration of Failure Mode and Effect Analysis (FMEA) with a Fuzzy approach to address subjectivity in risk assessment. Conventional RPN calculations showed the highest values for cracked prints (240), imprecision (150), and ink not adhering (75). The application of Fuzzy FMEA yielded more accurate and continuous FRPN values, namely cracked prints (249.5), imprecision (158), and ink not adhering (81.5). Proposed improvements include strict supplier selection, the use of periodic temperature thermometers, fabric pre-press techniques, and scheduling routine machine maintenance. The implementation of these steps is expected to minimize defective products and maintain customer confidence in product quality.